Singapore Management University Report to Stakeholders 2009 - 2010 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2009)
Since our inauguration in 2000, we have grown from a simple idea of a group of pioneers who came together - inspired by a new philosophy and approach towards undergraduate education - into a progressive, globally respected university that is widely recognised as a change agent and catalyst for innovation. Over the past 10 years, SMU has proven to be a successful experiment in Singapore’s efforts to strengthen and diversify its higher education sector. We have lived up to our promise of making a difference to our society through the graduates we have produced, through our engagement with the local community, and through our international contributions to academic scholarship.